2016
DOI: 10.1111/cas.12887
|View full text |Cite
|
Sign up to set email alerts
|

Exome‐wide single‐base substitutions in tissues and derived cell lines of the constitutive Fhit knockout mouse

Abstract: Loss of expression of Fhit, a tumor suppressor and genome caretaker, occurs in preneoplastic lesions during development of many human cancers. Furthermore, Fhit-deficient mouse models are exquisitely susceptible to carcinogen induction of cancers of the lung and forestomach. Due to absence of Fhit genome caretaker function, cultured cells and tissues of the constitutive Fhit knockout strain develop chromosome aneuploidy and allele copy number gains and losses and we hypothesized that Fhit deficient cells would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…T>C mutations may be due to the misincorporation of dUTP in place of dTTP, a consequence of TK1 downregulation in FHIT-deficient cells. This FHIT loss mutation profile is comparable to previously published mutation signatures reported for bladder cancer, human papillary kidney cancer, and an "age at diagnosis" signature, or aging signature, that represents accumulation of mutations in normal tissues over time [Alexandrov et al, 2013;Paisie et al, 2016]. As FHITdeficient genomes accumulate mutations, it is not surprising then that many of these mutations are found within important genes which, when altered, contribute to cellular transformation and preneoplastic changes.…”
Section: Fhit Loss-induced Cnas and Point Mutations Promote Clonal Exsupporting
confidence: 83%
See 3 more Smart Citations
“…T>C mutations may be due to the misincorporation of dUTP in place of dTTP, a consequence of TK1 downregulation in FHIT-deficient cells. This FHIT loss mutation profile is comparable to previously published mutation signatures reported for bladder cancer, human papillary kidney cancer, and an "age at diagnosis" signature, or aging signature, that represents accumulation of mutations in normal tissues over time [Alexandrov et al, 2013;Paisie et al, 2016]. As FHITdeficient genomes accumulate mutations, it is not surprising then that many of these mutations are found within important genes which, when altered, contribute to cellular transformation and preneoplastic changes.…”
Section: Fhit Loss-induced Cnas and Point Mutations Promote Clonal Exsupporting
confidence: 83%
“…FHIT-deficient liver tissues exhibited almost a 4-fold increase in total SBSs compared to wild-type liver tissue. Further examination of the types of transition and transversion mutations observed among these SBSs demonstrated that FHIT-deficient cells and tissues displayed prominent increases in C>T and T>C mutations, as well as slightly elevated levels of C>A, C>G, and T>A mutations [Paisie et al, 2016]. C>T mutations can be generated by spontaneous deamination or DNA replication errors.…”
Section: Fhit Loss-induced Cnas and Point Mutations Promote Clonal Exmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent report, the Huebner group analyzed whole exome sequences of Fhit -deficient tissues and cells and compared them to a control C57Bl6 genome, identifying hundreds of single-base substitutions associated with FHIT deficiency. The mutation signature is characterized by increased C>T and T>C mutations, in accordance with the signature identified in human malignancies [66]. …”
Section: Cfs Gene Products With Roles In the Ddrmentioning
confidence: 72%